A Mutation Outside the Dimerization Domain Causing Atypical STING-Associated Vasculopathy With Onset in Infancy - Saldanha, Rohit G.; Balka, Katherine R.; Davidson, Sophia; Wainstein, Brynn K.; Wong, Melanie; Macintosh, Rebecca; Loo, Christine K. C.; Weber, Martin A.; Kamath, Vasanth; , CIRCA; , AADRY; Moghaddas, Fiona; et al. (Frontiers in Immunology, 2018)
Background Mutations in the gene encoding stimulator of interferon genes (STING) underlie a type I interferon (IFN) associated disease, STING-associated vasculopathy with onset in infancy (SAVI). Patients suffer cutaneous vasculopathy and interstitial lung disease, but are not known to suffer life-threatening infection. Case We describe a child who presented with Pneumocystis jirovecii pneumonia in early life, from which he recovered. He went on to suffer failure to thrive, developmental delay, livedo reticularis, and vesicular rash, but without cutaneous vasculitis, and with normal C-reactive protein and erythrocyte sedimentation rates. At 3 years of age, he developed life-threatening pulmonary hypertension. Methods Whole genome sequencing (WGS) was performed using the Illumina HiSeqX10 platform and the Seave platform was used for bioinformatic analysis. mRNA expression of IFN-stimulated genes and inflammatory cytokines from peripheral blood mononuclear cells was determined by quantitative polymerase chain reaction. Luciferase assay was used to model IFNβ and NF-κB activity in vitro. Results WGS revealed a de novo mutation p.Arg284Ser in STING at an amino acid previously associated with SAVI. Although this mutation did not fall in the dimerization domain (DD), mRNA analysis revealed constitutive IFN-gene activation consistent with an interferonopathy, which correlated to STING activation in vitro. The patient was treated with corticosteroids and the JAK inhibitor Ruxolitinib, resulting in a rapid improvement of pulmonary hypertension, general well-being, and resolution of the IFN gene signature. However, he did go on to evolve a nasal septal erosion suggesting incomplete control of disease. Conclusion This case provides molecular evidence to support the p.Arg284Ser variant in STING exerting pathogenicity through a gain-of-function mechanism. The lack of cutaneous vasculitis or elevated systemic inflammatory markers, and the occurrence of an opportunistic infection are notable, and raise the possibility that variants outside the STING DD may potentially manifest with an atypical SAVI phenotype. Nevertheless, there was an objective clinical improvement in response to JAK inhibition.